Oxygen saturation at different altitudes in Nepal among adults - Shrestha, Sabina; Manoranjan, Aparajita; Man Shrestha, Sushan (Grande Medical Journal, 2020)
Introduction: The partial pressure of oxygen in the atmosphere decreases proportionately with an increase in the altitude. The study was done to compare the oxygen saturation of non-acclimatized adults going to different altitudes in Nepal. Materials and Methods: It was a descriptive observational study conducted on ten individuals of a medical team traveling to Humla district of Nepal for a multi-disciplinary medical camp. Oxygen saturation was measured at different altitudes i.e. in Kathmandu, Nepalgunj, in the flight at an altitude of 3360 meters and in Bargaun village of Humla district located at an altitude of 3300 meters. Mean pulse oximetry reading was calculated and compared. Results: Among the participants, age ranged from 24-57 years. Male to female ratio was 1.5:1. The mean SPO2 at Nepalgunj, Kathmandu, Bargaun of Humla and in the flight (at an altitude of 3360 meters) were 99.67 %, 97%, 91% and 87.4% respectively among the study participants. However, the difference in Oxygen saturation values at different altitudes among different gender and different age was not statistically significant. Conclusions: Oxygen saturation decreased linearly with the rise in altitude among all the study participants irrespective of age and gender.